Preparation method of self-adhesive low-temperature-resistant multifunctional conductive gel as well as product and application of self-adhesive low-temperature-resistant multifunctional conductive gel
Through the combination technology of sodium lignin sulfonate, transition metal salt and eutectic solvent, the structural stability and frost resistance of conductive hydrogels in low temperature environments were solved, and high mechanical properties and self-adhesion were prepared. The multifunctional conductive gel realizes strain sensing applications in low temperature environments and reduces preparation costs.
Patent Information
- Application Number
- CN202411232981.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-17
AI Technical Summary
The existing conductive hydrogels have poor structural stability, insufficient frost resistance and dehydration resistance in low temperature environments, and the preparation process is complex and costly, which limits their strain monitoring applications in complex environments.
The self-catalytic system is formed by sodium lignin sulfonate and transition metal salt, combined with eutectic solvents and water-soluble polymers, and self-adhesive low-temperature resistant multifunctional conductive gel is prepared through in-situ polymerization and solvent replacement technology to improve its mechanical properties , conductivity and adhesion.
The prepared gel has high mechanical properties, good self-adhesion and high ionic conductivity. It can maintain stable conductivity at -60°C. The preparation process is simple and low cost, and is suitable for large-scale applications.
Smart Images

Figure CN119320541A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flexible electronic materials, and in particular to a preparation method of a self-adhesive low-temperature-resistant multifunctional conductive gel, and a product and application thereof. Background Art
[0002] Conductive hydrogels have excellent mechanical ductility and high electrical conductivity, and have shown great potential for application in the fields of flexible wearable electronics and bionic devices. In general, hydrogel materials used for strain sensing need to provide: (1) high and stable electrical conductivity, fast and reliable real-time signal response to strain changes; (2) excellent mechanical properties, able to maintain the structural stability of the material during deformation by external force; (3) excellent adhesion, with strong adhesion to different substrates without the need for additional adhesives; (4) excellent temperature adaptability, especially reliability in cold environments. However, most current conductive hydrogel systems still have some disadvantages, including poor structural stability (low mechanical strength and flexibility), high water content (poor antifreeze and anti-dehydration properties), and weak self-adhesion to the substrate, which greatly limit the potential strain monitoring applications of such hydrogel materials under complex environmental conditions. In addition, traditional hydrogels require long-term heating or UV-induced polymerization to prepare, which limits the actual production and application of hydrogels. Therefore, it is imperative to develop strain sensing conductive gel materials that are suitable for low temperatures, mechanically reliable, and self-adhesive through a simple preparation strategy.
[0003] For conductive hydrogels, water, as the dispersion medium of the gel network, will inevitably freeze below zero degrees and evaporate at high temperatures, which will seriously damage the original mechanical properties, self-adhesion and conductivity of the hydrogel, severely limiting the subsequent application of the hydrogel. At present, researchers have proposed several methods to achieve the antifreeze performance of hydrogels, usually including organic gels and ionic gels. However, adding organic solvents as cryoprotectants to the hydrogel matrix will significantly reduce the conductivity of the gel; introducing ionic liquids (ILs) into the hydrogel network will enable the gel to obtain good antifreeze and ion conductivity, but its high toxicity may be detrimental to biological systems and the ecological environment, which runs counter to the biocompatibility and many applications of hydrogels, and ionic liquids have the problem of high cost of use, which is not suitable for large-scale commercial applications. How to prepare a strain sensing conductive gel material that is suitable for low temperatures, mechanically reliable, and self-adhesive, and reduce the preparation cost of strain sensing conductive gel materials, has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a self-adhesive low-temperature-resistant multifunctional conductive gel, and its product and application, so as to solve the problems existing in the above-mentioned prior art. The self-adhesive low-temperature-resistant multifunctional conductive gel prepared by the present invention has the advantages of good mechanical properties, excellent self-adhesive properties, high ionic conductivity, low temperature resistance, and low preparation cost.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a self-adhesive low-temperature-resistant multifunctional conductive gel, comprising the following steps:
[0007] (1) dissolving sodium lignin sulfonate in water, adding an organic monomer under low-speed stirring (300 rpm), adjusting the pH to 2-4, then slowly adding an initiator under high-speed stirring (1000 rpm), and removing unreacted impurities after in-situ polymerization under high-speed stirring (1000 rpm), and obtaining a LS / ICP mixed solution after rotary evaporation; dissolving the LS / ICP mixed solution and a transition metal salt in water to obtain a solution A;
[0008] (2) mixing a water-soluble polymer aqueous solution, acrylic acid, an initiator and water to obtain a solution B;
[0009] (3) At a certain rotation speed (400-600 rpm), solution A is added to solution B and stirred for 10-15 seconds to obtain a prepolymer solution, the prepolymer solution is allowed to stand to obtain a hydrogel, and the hydrogel is then immersed in a low eutectic solvent to obtain the self-adhesive, low-temperature-resistant multifunctional conductive gel.
[0010] Furthermore, in step (1), the ratio of the sodium lignin sulfonate, water, organic monomer and initiator is 1 g: 40-60 mL: 0.2-0.6 g: 1-4 mL;
[0011] The initiator includes an ammonium persulfate solution having a concentration of 0.1 wt.%;
[0012] The organic monomer includes any one of aniline, pyrrole and thiophene;
[0013] The solid content of the LS / ICP mixed solution is 3.0-5.0 wt.%;
[0014] The in-situ polymerization time is 24 hours.
[0015] Furthermore, in step (1), the mass ratio of the LS / ICP mixed solution, the transition metal salt and water in the solution A is (0.1-0.6):(0.04-0.06):(2-4);
[0016] The transition metal salt is FeCl3·6H2O.
[0017] Furthermore, in step (2), the water-soluble polymer in the water-soluble polymer aqueous solution includes any one of polyvinyl alcohol, polyethylene glycol and polyacrylamide;
[0018] The concentration of the water-soluble polymer aqueous solution is 6 to 10 wt.%;
[0019] The mass ratio of the water-soluble polymer aqueous solution, acrylic acid, initiator and water in the solution B is (1-3):(2-4):(0.02-0.04):(2-3);
[0020] The initiator includes ammonium persulfate.
[0021] Furthermore, in step (3), the mass ratio of solution A to solution B is 3:22.
[0022] Further, in step (3), the deep eutectic solvent comprises a ternary deep eutectic solvent of choline chloride-alcohol-Lewis acid;
[0023] The alcohol includes any one of ethylene glycol, 1,3-propylene glycol and glycerol;
[0024] The Lewis acid includes any one of LiCl, KCl, MgCl2, ZnCl2 and AlCl3;
[0025] The molar ratio of choline chloride, alcohol and Lewis acid in the choline chloride-alcohol-Lewis acid ternary deep eutectic solvent is 1:3:1.
[0026] Furthermore, in step (3), the volume ratio of the hydrogel to the low eutectic solvent is 1:(10-15);
[0027] The soaking time is 2 to 3 hours.
[0028] Deep eutectic solvents (DES) are usually composed of a eutectic mixture of a quaternary ammonium salt and a hydrogen bond donor (or metal salt), which generates larger asymmetric ions and has the advantages of lower melting point, higher electrical conductivity, good thermal stability and lower vapor pressure relative to the individual components. DES also has the advantages of low cost, easy manufacture and non-toxicity.
[0029] The deep eutectic solvent (DES) molecules can replace the water molecules in the gel and can interact with the polyacrylic acid / water-soluble polymer double network structure, Fe 3+ Additional hydrogen bonds, metal complexation / chelation, and van der Waals forces are formed between lignin and conductive polymer (LS / ICP). The combined effects of these non-covalent bonds synergistically enhance the mechanical strength of the gel.
[0030] Sodium lignin sulfonate has a dual role. First, it can be used as a dispersant to load conductive polymers for in-situ polymerization. Second, it can form a self-catalytic system with transition metal salt solutions to initiate acrylic acid polymerization at room temperature to prepare conductive hydrogels.
[0031] The catechol / quinone groups in sodium lignin sulfonate can combine with groups on the surface of various substrates, thereby giving the hydrogel good adhesion. In addition, the low eutectic solvent can replace the water in the hydrogel, so that the eutectic gel obtains stronger hydrogen bonds than the hydrogel, thereby significantly improving the adhesion strength of the conductive gel.
[0032] Through solvent replacement, the low eutectic solvent can enter the gel network, forming new water-EG hydrogen bonds and non-covalent bonds such as metal complexation, thereby effectively improving the antifreeze properties of the hydrogel.
[0033] The second technical solution of the present invention: a self-adhesive low-temperature-resistant multifunctional conductive gel prepared by the above-mentioned preparation method.
[0034] The third technical solution of the present invention: an application of the above-mentioned self-adhesive low-temperature-resistant multifunctional conductive gel in the preparation of sensors.
[0035] Furthermore, the sensor comprises a strain sensor.
[0036] The present invention discloses the following technical effects:
[0037] (1) The self-adhesive low-temperature-resistant multifunctional conductive gel prepared by the present invention has the advantages of good mechanical properties, excellent self-adhesive properties, high ionic conductivity, low-temperature resistance, low preparation cost, simple and safe preparation process, etc. It can be used for low-temperature-resistant strain sensors and is expected to be widely used.
[0038] (2) The present invention uses lignin loaded with conductive polymer (LS / ICP) and metal iron ions to form a self-catalytic system, which plays a key role in catalyzing the polymerization of acrylic acid monomers at room temperature and cross-linking with the water-soluble polymer network to form a polyacrylic acid / water-soluble polymer double network hydrogel. The π electron system of the conductive polymer can undergo electron transitions, allowing electrons to be transferred between molecules. The metal ions in the gel (iron ions and metal ions in the low eutectic solvent) can form a coordination ion system with the electrons in the conductive polymer, thereby increasing the carrier concentration in the system and enhancing the transfer of electrons between conductive polymers, thereby improving the conductivity. In addition, the metal ions can form coordination bonds with the conductive polymer, changing the spatial conformation of the polymer, thereby facilitating electron transmission and giving the gel good conductivity.
[0039] (3) The self-adhesive, low-temperature-resistant multifunctional conductive gel prepared by the present invention can have an ionic conductivity of up to 4.4 mS / cm at room temperature, and the ionic conductivity can be stabilized at 1.16 mS / cm at a low temperature of -60°C; the self-adhesive, low-temperature-resistant multifunctional conductive gel prepared by the present invention also has excellent mechanical properties (fracture strain can reach 460%, and fracture strength can reach 98.2 kPa), self-adhesion (adhesion strength on paper is 14.6 kPa), self-healing properties (after healing for 7 hours, the mechanical self-healing efficiency of the gel reaches a maximum value of 88.8%) and anti-ultraviolet performance (ultraviolet light blocking rate at 365 nm is as high as 99.9%).
[0040] (4) The self-adhesive, low-temperature-resistant multifunctional conductive gel prepared by the present invention has reliable self-adhesive properties and excellent strain sensing performance. The response time and relaxation time of the sensor (i.e., the self-adhesive, low-temperature-resistant multifunctional conductive gel) are 253 ms and 232 ms, respectively, which can meet the needs of real-time motion detection and can cope with continuous stretching cycles (more than 100 cycles) under a fixed strain of 50%. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 This is a schematic diagram of the preparation process of the self-adhesive low-temperature-resistant multifunctional conductive gel of the present invention;
[0043] Figure 2 The morphologies and transmission electron microscope images of the gels prepared in Example 1 and Comparative Example 2 of the present invention, wherein a is the morphology of the gel prepared in Example 1, b is the transmission electron microscope image of the gel prepared in Example 1, c is the morphology of the gel prepared in Comparative Example 2, and d is the transmission electron microscope image of the gel prepared in Comparative Example 2;
[0044] Figure 3 Comparison of the adhesion of 0LS / ICP prepared in Comparative Example 1 of the present invention, 0.2LS / ICP prepared in Example 1, 0.4LS / ICP prepared in Example 2, 0.6LS / ICP prepared in Example 3, and DES-0.2LS / ICP prepared in Example 1;
[0045] Figure 4The elastic modulus, fracture strength and toughness of 0LS / ICP prepared in Comparative Example 1 of the present invention, 0.2LS / ICP prepared in Example 1, 0.4LS / ICP prepared in Example 2, 0.6LS / ICP prepared in Example 3, DES-0.2LS / ICP prepared in Example 1 and DES-0.4LS / ICP prepared in Example 2 are compared;
[0046] Figure 5 The conductivity of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 of the present invention at different temperatures;
[0047] Figure 6 The self-healing performance of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 of the present invention;
[0048] Figure 7 The anti-ultraviolet performance of 0.2LS / ICP, 0.4LS / ICP, 0.1LS / ICP and self-adhesive low-temperature resistant multifunctional conductive gel prepared in Examples 1 to 2 and 4 of the present invention;
[0049] Figure 8 The adhesion of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 of the present invention on the skin;
[0050] Fig. 9 The adhesion of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 on the surfaces of various substrates. DETAILED DESCRIPTION
[0051] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0052] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0053] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0054] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0055] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0056] In a first aspect, the present invention provides a method for preparing a self-adhesive low-temperature-resistant multifunctional conductive gel, comprising the following steps:
[0057] (1) dissolving sodium lignin sulfonate in water, adding an organic monomer (ICP) under low-speed stirring (300 rpm), adjusting the pH to 2-4, then slowly adding an initiator under high-speed stirring (1000 rpm), and removing unreacted impurities after in-situ polymerization (i.e., in-situ copolymerization) under high-speed stirring (1000 rpm), and obtaining a LS / ICP mixed solution after rotary evaporation; dissolving the LS / ICP mixed solution and a transition metal salt in water (oxidation reaction occurs) to obtain a solution A;
[0058] (2) mixing a water-soluble polymer aqueous solution (second polymer), acrylic acid (AA), an initiator and water to obtain a solution B;
[0059] (3) At a certain rotation speed (400-600 rpm), solution A is added to solution B and stirred for 10-15 seconds to obtain a prepolymer solution. The prepolymer solution is allowed to stand to obtain a hydrogel (rapid polymerization at room temperature). The hydrogel is then immersed in a low eutectic solvent (DES) to obtain a self-adhesive, low-temperature-resistant multifunctional conductive gel.
[0060] Schematic diagram of the preparation process of self-adhesive low-temperature resistant multifunctional conductive gel Figure 1 .
[0061] In step (1) of the present invention, the dosage ratio of sodium lignin sulfonate, water, organic monomer and initiator is 1g:40-60mL:0.2-0.6g:1-4mL; the initiator includes an ammonium persulfate solution with a concentration of 0.1wt.%; the organic monomer includes any one of aniline, pyrrole and thiophene; the solid content of the LS / ICP mixed solution is 3.0-5.0wt.%; and the in-situ polymerization time is 24h.
[0062] In step (1) of the present invention, the mass ratio of LS / ICP mixed solution, transition metal salt and water in solution A is (0.1-0.6):(0.04-0.06):(2-4); the transition metal salt is FeCl3·6H2O.
[0063] In step (2) of the present invention, the water-soluble polymer in the water-soluble polymer aqueous solution includes any one of polyvinyl alcohol, polyethylene glycol and polyacrylamide; the concentration of the water-soluble polymer aqueous solution is 6 to 10 wt.%; the mass ratio of the water-soluble polymer aqueous solution, acrylic acid, initiator and water in solution B is (1 to 3): (2 to 4): (0.02 to 0.04): (2 to 3); and the initiator includes ammonium persulfate.
[0064] In step (3) of the present invention, the mass ratio of solution A to solution B is 3:22.
[0065] In step (3) of the present invention, the low eutectic solvent includes a ternary low eutectic solvent of choline chloride-alcohol-Lewis acid; the alcohol includes any one of ethylene glycol, 1,3-propylene glycol and glycerol; the Lewis acid includes any one of LiCl, KCl, MgCl2, ZnCl2 and AlCl3; and the molar ratio of choline chloride, alcohol and Lewis acid in the ternary low eutectic solvent of choline chloride-alcohol-Lewis acid is 1:3:1.
[0066] In step (3) of the present invention, the volume ratio of the hydrogel to the low eutectic solvent is 1:(10-15); and the immersion time is 2-3 hours.
[0067] In a second aspect, the present invention provides a self-adhesive, low-temperature-resistant, multifunctional conductive gel prepared by the above-mentioned preparation method.
[0068] The third aspect of the present invention provides a use of the self-adhesive low-temperature-resistant multifunctional conductive gel in the preparation of a sensor.
[0069] The sensor of the present invention comprises a strain sensor.
[0070] The "room temperature" or "normal temperature" in the present invention is 25±2°C unless otherwise specified.
[0071] Example 1
[0072] A method for preparing a self-adhesive low-temperature-resistant multifunctional conductive gel:
[0073] (1) 1 g of sodium lignin sulfonate was dissolved in 50 mL of deionized water, and 0.3 g of organic monomer 3,4-ethylenedioxythiophene was added dropwise under low-speed stirring (300 rpm), and then the pH was adjusted to 2 with HCl solution. Then, 4 mL of 2.5 wt.% ammonium persulfate (APS) solution was slowly added under high-speed stirring (1000 rpm), and in-situ polymerization was carried out at room temperature and high-speed stirring (1000 rpm) for 2 h to remove unreacted impurities, and finally, rotary evaporation was performed in a pear-shaped flask to obtain a lignin / conductive polymer mixed solution (LS / ICP mixed solution) with a solid content of 4.0 wt.%.
[0074] Solution A was obtained by dissolving 0.2 g of LS / ICP mixed solution and 0.06 g of FeCl3·6H2O in 3 g of deionized water.
[0075] (2) 2 g of the second polymer aqueous solution (polyvinyl alcohol solution with a concentration of 10 wt.%), 2.5 g of acrylic acid, and 0.025 g of ammonium persulfate were dissolved in 2.5 g of deionized water to obtain solution B.
[0076] (3) Pour 1.2 g of solution A into 8.8 g of solution B at a rotation speed of 500 rpm and stir for 10 seconds to obtain a prepolymer solution; pour the prepolymer solution into a polytetrafluoroethylene mold and let it stand at room temperature to form a hydrogel (i.e., 0.2LS / ICP); place the prepared hydrogel in a choline chloride-alcohol-Lewis acid ternary low eutectic solvent (the volume ratio of the hydrogel to the choline chloride-alcohol-Lewis acid ternary low eutectic solvent is 1:10) and soak it for 3 hours to obtain a self-adhesive, low-temperature-resistant multifunctional conductive gel (i.e., DES-0.2LS / ICP).
[0077] The choline chloride-alcohol-Lewis acid ternary deep eutectic solvent (DES) is composed of choline chloride, ethylene glycol and LiCl in a molar ratio of 1:3:1.
[0078] Preparation method of low eutectic solvent: under a constant temperature of 90° C., choline chloride, ethylene glycol and lithium chloride in a molar ratio of 1:3:1 are stirred to form a uniform and transparent solution, and then placed in a desiccator for use.
[0079] Example 2
[0080] The same as Example 1, except that the amount of LS / ICP mixed solution in solution A prepared in step (1) is 0.4 g; the obtained hydrogel is 0.4LS / ICP; and the obtained self-adhesive low-temperature-resistant multifunctional conductive gel is DES-0.4LS / ICP.
[0081] Example 3
[0082] The same as Example 1, except that the amount of LS / ICP mixed solution in solution A prepared in step (1) is 0.6 g; the obtained hydrogel is 0.6LS / ICP; and the obtained self-adhesive low-temperature-resistant multifunctional conductive gel is DES-0.6LS / ICP.
[0083] Example 4
[0084] The same as Example 1, except that the amount of LS / ICP mixed solution in solution A prepared in step (1) is 0.1 g; the obtained hydrogel is 0.1LS / ICP; and the obtained self-adhesive low-temperature-resistant multifunctional conductive gel is DES-0.1LS / ICP.
[0085] Comparative Example 1
[0086] Preparation method of 0LS / ICP:
[0087] Same as Example 1, except that the amount of LS / ICP added is 0.
[0088] Comparative Example 2
[0089] 2.5 g acrylic acid monomer, 2 g 10 wt.% polyvinyl alcohol solution, 0.2 g LS / ICP and 0.025 g ammonium persulfate (initiator) were dissolved in 10 g deionized water (reacted in a 30 mL sample bottle) to form a homogeneous solution, and then crosslinked at 50° C. for 5 h to form a hydrogel.
[0090] Effect Example 1
[0091] The apparent morphology and transmission electron microscopy images of the gels prepared in Example 1 and Comparative Example 2 are shown in Figure 2 ; Figure 2 In the figure, a is the apparent morphology of the gel prepared in Example 1, b is the transmission electron microscopy image of the gel prepared in Example 1, c is the apparent morphology of the gel prepared in Comparative Example 2, and d is the transmission electron microscopy image of the gel prepared in Comparative Example 2.
[0092] from Figure 2 It can be seen that the surface roughness of the gel prepared in Example 1 is greater than that in Comparative Example 2. This phenomenon is caused by the replacement process between water and the low eutectic solvent. The rough surface can increase the contact area with the substrate, thereby enhancing the adhesion performance.
[0093] Effect Example 2
[0094] (1) Comparison of the adhesion of 0LS / ICP prepared in Comparative Example 1, 0.2LS / ICP prepared in Example 1, 0.4LS / ICP prepared in Example 2, 0.6LS / ICP prepared in Example 3, and DES-0.2LS / ICP prepared in Example 1. Figure 3 .
[0095] Adhesion test method: Use UH6502 universal testing machine to perform lap shear test, set the speed to 50mm min -1 .
[0096] The calculation formula of adhesion strength (τ, kPa) is as follows:
[0097]
[0098] In the formula, F represents the maximum breaking strength (N), and S represents the effective adhesion area between the gel and the substrate (cm 2 ).
[0099] from Figure 3 It can be seen that with the increase of LS / ICP content and the occurrence of water and low eutectic solvent in the replacement process, the adhesion strength of the hydrogel on the rubber increases from 4.65±0.3kPa to 6.9±0.6kPa. This is because the catechol / quinone groups in LS can combine with the groups on the surface of the substrate, thus giving the hydrogel good adhesion.
[0100] (2) The elastic modulus, fracture strength and toughness of 0LS / ICP prepared in Comparative Example 1, 0.2LS / ICP prepared in Example 1, 0.4LS / ICP prepared in Example 2, 0.6LS / ICP prepared in Example 3, DES-0.2LS / ICP prepared in Example 1 and DES-0.4LS / ICP prepared in Example 2 are compared. Figure 4 .
[0101] Fracture strength test method: Use UH6502 universal testing machine to perform tensile test on gel sample (national standard dumbbell shape, 5mm wide, 2mm thick, 30mm long), and set the test speed to 20mm min -1 The toughness (T) is obtained by integrating the area of the stress-strain curve up to the fracture point, and the calculation formula is as follows:
[0102]
[0103] Where T is the toughness of the gel (kJ·m -3 ), ε and u(ε) represent the tensile strain and stress (kPa) at the maximum fracture, respectively.
[0104] from Figure 4It can be seen that with the increase of LS / ICP content, the fracture strength of the hydrogel weakened from 55±2.5kPa to 29±1.08kPa, and its elastic modulus and toughness showed a decreasing and increasing trend with the increase of LS / ICP content, respectively. This is mainly because LS / ICP particles will destroy the covalent cross-linking network of the hydrogel, making its internal structure looser and more disordered, and the gel molecular chains have a larger activity space during the stretching process, resulting in a decrease in the elastic modulus and an increase in toughness; on the other hand, the fracture strength (98.2±3.7kPa) and tensile strain (460%) of the eutectic gel (self-adhesive low-temperature resistant multifunctional conductive gel) are higher than those of the hydrogel before solvent replacement (tensile strain of 0.2LS / ICP is 415%), which is mainly because the increase in intermolecular non-covalent bonds (mainly hydrogen bonds) between DES and functional groups (-OH and -COOH) in the hydrogel leads to the improvement of its mechanical properties.
[0105] Effect Example 3
[0106] (1) The conductivity of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 at different temperatures is shown in FIG. Figure 5 .
[0107] Conductivity test method: Using Chenhua CH660D electrochemical workstation, the conductivity of the gel was measured by electrochemical impedance spectroscopy (EIS), with a test frequency range of 0.01 to 100 kHz and an amplitude of 5 mV. The conductivity calculation formula of the gel is as follows:
[0108]
[0109] Where D, S and R represent the thickness (cm), area (cm 2 ) and electrochemical impedance (Ω) of the gel electrode.
[0110] from Figure 5 It can be seen that when the temperature drops from 25°C to -60°C, the conductivity of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 decreases from 4.3 mS·cm -1 Down to 1.2mS·cm -1 , but still has stable conductivity at -60℃.
[0111] (2) The self-healing properties of the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 are shown in Figure 6 .
[0112] Self-healing performance test method: Cut the hydrogel into two halves and then connect them together. After different time periods, test the breaking strength of the sample.
[0113] from Figure 6It can be seen that with the increase of healing time, the healing efficiency gradually increases. After 7 hours of healing, the mechanical self-healing efficiency of the gel reaches the highest value (88.8%). This self-healing ability is mainly attributed to the reversible coordination bonds and hydrogen bonds in the gel.
[0114] (3) The anti-ultraviolet performance of 0.2LS / ICP, 0.4LS / ICP, 0.1LS / ICP and self-adhesive low-temperature resistant multifunctional conductive gel prepared in Examples 1 to 2 and 4 is shown in FIG. Figure 7 .
[0115] Figure 7 The transmittances of 0.1LS / ICP, 0.2LS / ICP and 0.4LS / ICP at 365nm were 0.21%, 0.17% and 0.09% respectively; after solvent replacement, the transmittances of the obtained eutectic gels DES-0.1LS / ICP, DES-0.2LS / ICP and DES-0.4LS / ICP at 365nm were close to zero.
[0116] Anti-ultraviolet performance test method: Place a gel sample with a thickness of 2 mm in a UV-visible-near infrared spectrophotometer and test the transmittance of the sample at a wavelength of 200-800 nm.
[0117] from Figure 7 It can be seen that the UV blocking ability of the gel increases with the increase of LS / ICP content. This is because LS / ICP contains abundant UV absorbing functional groups, such as aromatic ring structure, conjugated structure and other chromophores, but these chromophores will affect the transparency of the gel. Compared with hydrogel, eutectic gel (self-adhesive low-temperature resistant multifunctional conductive gel after solute replacement) has higher UV blocking ability in the UV-A band. This improvement is mainly because after DES enters the gel network, it will produce conjugated and non-covalent bonds with various groups in the hydrogel network, thereby improving the UV blocking ability.
[0118] (4) The adhesion of the self-adhesive low-temperature-resistant multifunctional conductive gel (room temperature) prepared in Example 1 on the skin is shown in FIG. Figure 8 .
[0119] from Figure 8 As can be seen in the figure, the eutectic gel can adhere perfectly to human skin and can be peeled off cleanly.
[0120] (5) The adhesion strength of the self-adhesive low-temperature-resistant multifunctional conductive gel (room temperature) prepared in Example 1 to different substrates is shown in FIG. Fig. 9 .
[0121] from Fig. 9It can be seen that the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 has reliable adhesion properties on the surfaces of various substrates. The reason is that the self-adhesive low-temperature-resistant multifunctional conductive gel prepared in Example 1 has a large number of polar functional groups, such as hydroxyl groups, carboxyl groups, etc. These functional groups can form hydrogen bonds with silanol groups (Si-OH) on the glass surface, so it has good adhesion to glass; the main component of paper is cellulose, which can provide a high density of hydroxyl binding sites, thereby forming strong hydrogen bonds with the gel, so that the gel has significant adhesion to smooth paper (the adhesion strength of the gel on paper is the highest (14.6±0.6kPa)).
[0122] Table 1 Comparison of gel properties
[0123]
[0124]
[0125] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a self-adhesive low-temperature-resistant multifunctional conductive gel, characterized in that: The following steps are involved: Adding organic monomers to the sodium lignin sulfonate solution, adjusting the pH to 2-4, then adding an initiator, in-situ polymerization, to obtain a LS / ICP mixed solution; dissolving the LS / ICP mixed solution and a transition metal salt in a solvent to obtain a solution A; Mixing a water-soluble polymer solution, acrylic acid, an initiator and a solvent to obtain a solution B; Solution A is added to solution B, stirred evenly and then allowed to stand to obtain a hydrogel, and then the hydrogel is immersed in a low eutectic solvent to obtain the self-adhesive, low-temperature-resistant multifunctional conductive gel.
2. The preparation method according to claim 1, characterized in that: The mass ratio of sodium lignin sulfonate to organic monomer in the sodium lignin sulfonate solution is 1:(0.2-0.6); The initiator includes ammonium persulfate; The organic monomer includes any one of aniline, pyrrole and thiophene; The solid content of the LS / ICP mixed solution is 3.0-5.0 wt.%; The in-situ polymerization time is 24 hours.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the LS / ICP mixed solution, the transition metal salt and the solvent in the solution A is (0.1-0.6):(0.04-0.06):(2-4).
4. The preparation method according to claim 1, characterized in that: The water-soluble polymer in the water-soluble polymer solution includes any one of polyvinyl alcohol, polyethylene glycol and polyacrylamide; The concentration of the water-soluble polymer solution is 6 to 10 wt.%; The mass ratio of the water-soluble polymer solution, acrylic acid, initiator and solvent in the solution B is (1-3):(2-4):(0.02-0.04):(2-3).
5. The preparation method according to claim 1, characterized in that: The solvent includes water; The mass ratio of solution A to solution B is 3:
22.
6. The preparation method according to claim 1, characterized in that: The deep eutectic solvent comprises a ternary deep eutectic solvent of choline chloride-alcohol-Lewis acid; The alcohol includes any one of ethylene glycol, 1,3-propylene glycol and glycerol; The Lewis acid includes any one of LiCl, KCl, MgCl2, ZnCl2 and AlCl3; The molar ratio of choline chloride, alcohol and Lewis acid in the choline chloride-alcohol-Lewis acid ternary deep eutectic solvent is 1:3:
1.
7. The preparation method according to claim 1, characterized in that: The volume ratio of the hydrogel to the low eutectic solvent is 1:(10-15); The soaking time is 2 to 3 hours.
8. A self-adhesive, low-temperature-resistant multifunctional conductive gel prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the self-adhesive low-temperature-resistant multifunctional conductive gel according to claim 8 in the preparation of a sensor.
Citation Information
Patent Citations
Self-healing, anti-freezing and self-adhesive conductive ion hydrogel with birefringence characteristic as well as preparation method and application of self-healing, anti-freezing and self-adhesive conductive ion hydrogel
CN115368509A
Preparation method and application of lignin-polypyrrole conductive hydrogel material
CN117777494A
Ionic gel based on poly (3, 4-ethylenedioxythiophene) / sodium lignin sulfonate and preparation method and application thereof
CN117946420A
Cited By
Preparation method and application of lignin-based zero-swelling hydrogel adsorbent
CN119875035A